Tuning Magnetic Properties of Coxni100-X Nanodots: Micromagnetic Insights for Tailoring Enhanced Electrochemical Performance in Energy Storage Devices - Escrig-Murua, J; Saavedra-Díaz, E (American Chemical Society, 2024)
We conducted an integral study based on micromagnetic simulations and experiments to systematically investigate the quasi-static and dynamic magnetic characteristics of CoxNi100-x nanodots, varying the Co composition. We compared the magnetic properties of both ideal and real defective circular geometries, employing phase diagrams, hysteresis loops, and magnetization reversal modes for a comprehensive analysis. Our study highlights distinct alterations in coercivity and remanence between ideal and real defective geometries, while the S-mode of reversal is observed in both cases. Notably, our simulations underscore the remarkable sensitivity of magnetic properties to edge defects and the Co content in the alloy. This research underscores the essential role of micromagnetic simulations in tailoring the Co composition of the alloy, thereby fine-tuning the material’s magnetic hardness for enhanced performance in electrochemical applications, particularly as electrodes in energy storage devices. © 2024 American Chemical Society.